Purported use and self-awareness of cognitive and metacognitive foreign language reading strategies in tertiary education in Mozambique - Cabinda, Manuel (Afrika Focus, 2016)
This paper explores the results of a Survey of Reading Strategies (SORS)-based questionnaire administered to 28 university student participants. The study is carried out in a post-colonial multilingual context, Mozambique. The main aims of the paper are to assess the degree of purported use and awareness of participants own use of reading comprehension skills and strategies in a foreign language (English). The participants were tested for their reading text comprehension using an IELTS comprehension test (Cabinda, 2013). The results revealed low reading comprehension levels. Results contrast with results from the SORS-based questionnaire (Cabinda, 2013) which revealed claims of use of a wide range of cognitive, metacognitive and supply strategies – aspects of high level reading ability and text comprehension. Conclusions show that the participants used or claimed to chiefly use metacognitive and cognitive reading strategies equally, matching the behaviour of good readers, but they also reported a high degree of supply strate- gies to construe meaning from text, mainly code-switching, translation and cognates. The latter cofirms results from studies by Jimenez et al. (1995, 1996) and Zhang & Wu (2009), yet do not conclusively show a correlation between the participants’ degree of text comprehension and their effective use of reading skills and strategies to construe meaning. Further conclusions show that the reported high use of these L1 (Portuguese or other) related supply strategies (not used by English L1 readers) does not aid their reading comprehension. Key words : EFL, reading strategies, cognition, metacognition, awareness